The Quaternary Active Faults Database of Iberia (QAFI v.2.0) - García-Mayordomo, J.; Insua-Arévalo, J.M.; Martínez-Díaz, J.J.; Jiménez-Díaz, A.; Martín-Banda, R.; Martín-Alfageme, S.; Álvarez-Gómez, J.A.; Rodríguez-Peces, M.; Pérez-López, R.; Rodríguez-Pascua, M.A.; Masana, E.; Perea, H.; et al. (Journal of Iberian Geology, 2012)
The Quaternary Active Faults Database of Iberia (QAFI) is an initiative lead by the Institute of Geology and Mines of Spain (IGME) for building a public repository of scientific data regarding faults having documented activity during the last 2.59 Ma (Quaternary). QAFI also addresses a need to transfer geologic knowledge to practitioners of seismic hazard and risk in Iberia by identifying and characterizing seismogenic fault-sources. QAFI is populated by the information freely provided by more than 40 Earth science researchers, storing to date a total of 262 records. In this article we describe the development and evolution of the database, as well as its internal architecture. Additionally, a first global analysis of the data is provided with a special focus on length and slip-rate fault parameters. Finally, the database completeness and the internal consistency of the data are discussed. Even though QAFI v.2.0 is the most current resource for calculating fault-related seismic hazard in Iberia, the database is still incomplete and requires further review.